2019
DOI: 10.1007/s40071-019-00247-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Corbicula fluminea on the nutrient concentration and phytoplankton biomass of tropical reservoirs

Abstract: Invasive bivalves are known to negatively impact aquatic ecosystems across the globe. Previous research has demonstrated invasive bivalves can shift nutrients from the water column to the sediment, harm native bivalves, and reduce phytoplankton biomass. However, bivalve effects vary with species and the region where the invasion occurs. Therefore, we used mesocosm experiments to examine the impact of invasive Corbicula fluminea on nutrient concentration and phytoplankton biomass in the water column of mesotrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
0
1
1
Order By: Relevance
“…However, some studies have shown that the disturbance of C. fluminea will increase the amount of nutrients in water [65], but only at densities >1000 ind m −2 [66]. The density of C. fluminea in our experiment was <320 ind m −2 (816 g m −2 ), which explains why they improved rather than deteriorated the water quality.…”
Section: Discussioncontrasting
confidence: 54%
“…However, some studies have shown that the disturbance of C. fluminea will increase the amount of nutrients in water [65], but only at densities >1000 ind m −2 [66]. The density of C. fluminea in our experiment was <320 ind m −2 (816 g m −2 ), which explains why they improved rather than deteriorated the water quality.…”
Section: Discussioncontrasting
confidence: 54%
“…Como consecuencia, se reduce el alimento disponible para otros organismos suspensívoros. La productividad del fitoplancton está además afectada indirectamente por la influencia de la especie en la dinámica de los nutrientes, particularmente en el ciclo del nitrógeno (Beaver et al 1991;Chappell et al 2019). C. fluminea puede causar incremento de este nutriente en el agua mediante excreción/liberación de formas inorgánicas (principalmente amonio) (Bartoli et al 2003;Ruginis et al 2014) y por transferencia del sedimento a la columna de agua a través de la bioturbación (Coelho et al 2018), o disminución como consecuencia de la filtración de nutrientes de la columna de agua (Patrick et al 2017).…”
Section: Efectos De Corbicula Fluminea Sobre Los Ensambles De Macroinvertebradosunclassified